Kartläggning av rapporterade olyckor med djurtransporter i dagspress i Sverige - Thernell, Henrietta (2014)
When farm animals are transported there are several factors that can affect their welfare. If the vehicle has an accident the welfare of the animals transported will probably be compromised.